2017
DOI: 10.1016/j.bbmt.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Age over Fifty-Five Years at Diagnosis Increases Risk of Second Malignancies after Autologous Transplantation for Patients with Hodgkin Lymphoma

Abstract: The impact of age at diagnosis on outcomes of patients with Hodgkin lymphoma (HL) undergoing autologous hematopoietic transplantation (auto-HCT) is unclear. We retrospectively evaluated the impact of age on outcomes of 310 consecutive patients with relapsed/refractory HL who underwent auto-HCT between January 1996 and December 2010 with carmustine, etoposide, cytarabine, and melphalan conditioning therapy. Patients were stratified into ≤ 55 and >55-year-age groups based on age at diagnosis. At a median follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In their analysis of 154 patients who received ASCT, Minn et al [34] found a 15-year cumulative incidence of SM of 12%, but the RR of SM was similar to cHL patients who did not receive ASCT. Age >55 years at diagnosis of cHL was identified by Pingali et al [32] as a risk factor for SM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In their analysis of 154 patients who received ASCT, Minn et al [34] found a 15-year cumulative incidence of SM of 12%, but the RR of SM was similar to cHL patients who did not receive ASCT. Age >55 years at diagnosis of cHL was identified by Pingali et al [32] as a risk factor for SM.…”
Section: Discussionmentioning
confidence: 97%
“…Pingali et al [32] reported the results of a retrospective study involving 310 patients with relapsed or refractory cHL who received ASCT with BEAM conditioning and an ifosfamide-etoposide based mobilization. After a median follow-up of 80 months (range 1-180 months), the cumulative incidence of SM was 11% in the cohort, with 13 sMDS/sAML, three basal cell carcinomas, two squamous cell cancers, one prostate cancer, one myeloproliferative neoplasm, and one sarcoma.…”
Section: Different Therapies Including Ct and Rtmentioning
confidence: 99%